2019
DOI: 10.1055/s-0039-1690108
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of 1-Substituted 1,2,3,4-Tetrahydroisoquinolines through 1,3-Dipolar Cycloaddition by a Chiral Phosphoric Acid

Abstract: A new approach is described for the asymmetric synthesis of 1-substituted 1,2,3,4-tetrahydroisoquinolines that is based on the enantioselective 1,3-dipolar cycloaddition reaction of a nitrone and a vinyl ether in the presence of a chiral phosphoric acid that gives the chiral tetrahydroisoquinolines in high yields and with high enantioselectivities. 1H and 31P NMR analyses of the mixture of nitrone and chiral phosphoric acid suggest the formation of a 1:1 complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Where additional comparison data is available, several other studies involving imine-type electrophiles (C=N-R) have shown the importance of including TCYP in a catalyst evaluation despite the structural similarities with TRIP. [32][33][34][35][36][37][38][39][40][41] By performing this type of analysis with similarly related electrophiles, azo compounds, [42][43][44][45][46] precedent shows TCYP to be a top performer. Continued expansion of this comparative analysis demonstrates TCYP to be effective in condensation, 47,48 halogenation [49][50][51][52] and organometallic reactions.…”
Section: Inverse Catalyst Designmentioning
confidence: 99%
“…Where additional comparison data is available, several other studies involving imine-type electrophiles (C=N-R) have shown the importance of including TCYP in a catalyst evaluation despite the structural similarities with TRIP. [32][33][34][35][36][37][38][39][40][41] By performing this type of analysis with similarly related electrophiles, azo compounds, [42][43][44][45][46] precedent shows TCYP to be a top performer. Continued expansion of this comparative analysis demonstrates TCYP to be effective in condensation, 47,48 halogenation [49][50][51][52] and organometallic reactions.…”
Section: Inverse Catalyst Designmentioning
confidence: 99%
“…[30] In this context, Akiyama and co-workers developed the chiral phosphoric acid catalyzed enantioselective synthesis of 1-substituted 1,2,3,4-tetrahydroisoquinolines ( 8) by 1,3dipolar cycloaddition reaction (Scheme 2). [31] In the presence of CPA, only various nitrones (6) with electron-withdrawing groups at the 5-or 7-position of the isoquinoline readily gave the desired product, chiral 1-substituted 1,2,3,4-tetrahydroisoquinolines, in moderate yields (46-75 %), excellent exo selectivity (exo/endo ratios; up to 100 : 0) and moderate to good enantioselectivities (75-87 % ee), while nitrones with electrondonating groups and vinyl ethers (7) do not undergo this reaction under established reaction conditions. With the mediation of chiral phosphoric acid, 6 and 7 form the intermediate (In-1), which is then deprotonated by the phosphonate ion to give product 8.…”
Section: Stereoselective 13-dipolar Cycloadditionmentioning
confidence: 99%